Dynamics of trace and rare earth elements during long-term (over 4 years) decomposition in Scots pine and Norway spruce forest stands, Southern Sweden - Gautam, Mukesh K.; Berg, Björn; Lee, Kwang-Sik; Nilsson, Torbjörn; Shin, Hyung Seon (Frontiers in Environmental Science, 2023)
The temporal dynamics of 33 major, trace and rare earth elements (REEs) was studied in the Swedish Norway spruce-NSL (Picea abies) and Scots pine-SPL (Pinus sylvestris) litters with the aim to assess their release and accumulation dynamics. Litter bags (8×8cm) were incubated in paired monoculture stands of both the species for upto five years from 1979-1984 according to a randomized block design comprising 25 blocks (1×1 m) within an area of 625 m 2 . Decomposition rate was slightly higher for SPL (k = 0.315) compared to that of NSL (k= 0.217). During litter decomposition, until ~70% accumulated mass loss (AML), concentration of trace elements increased >50% in both litter types relative to initial concentrations. The pattern of concentration change was non-linear, and polynomial quadratic regression between concentration change and AML resulted in a significant relationships (adj R 2 = 0.20-0.97; P = 0.15-<0.0001). The changes in concentration and amount of trace elements resulted in two main types of dynamics; (i) both concentration and amount increased for Fe, Al, Ti, Cu, Mo, V, Zr, Sb, As, Cs, Pb, Th and U;(ii) concentration increased but amount decreased for Ni, Zn, Li and Sr. REEs' amounts increased ~3-fold to 99-fold between the beginning and end of incubations suggesting accumulation during litter decomposition. Dynamics of different REEs were similar in their patterns of change in the two litters. Different REEs, had generally identical patterns of change during incubation, which is